Differentiation of the solid-state NMR signals of gel, zeolite phases and water species in geopolymer-zeolite composites. Issue 2 (1st February 2017) - Greiser, Sebastian; Sturm, Patrick; Gluth, Gregor J.G.; Hunger, Michael; Jäger, Christian
Abstract: Geopolymer-zeolite composites were synthesized using a silica-rich industrial byproduct from chlorosilane production and sodium aluminate. Pastes were cured at 80 °C and 80% RH, and subsequently dried in two different climates: at 23 °C and 50% RH, and under vacuum. 1 H MAS, 23 Na MAS and 29 Si MAS NMR and XRD measurements were performed after the drying procedures as well as after subsequent aging. Zeolite Na-A was found beside traces of faujasite-type zeolite and zeolite EMT as major crystalline phases in the cured composites; the fraction of geopolymeric gel in the reaction products was determined to be ~18% on a molar basis. Various water species could be distinguished using 1 H MAS and 1 H- 29 Si CP MAS NMR, applying rotor-synchronized echo experiments. The largest fraction of the pore water resides in the α-cages of the zeolite Na-A and in the geopolymeric gel; in addition, water exists in the β-cages of the zeolites and adsorbed at sodium ions. The water species in α-cages and in the pores of the geopolymeric gel exhibit slightly different chemical shifts of 4.7 ppm and 4.9 ppm, respectively, in the 1 H MAS NMR spectra. Changes of the water content in the geopolymer pores of differently dried samples were observed and led to slightly varied chemical shifts in the 29 Si MAS NMR spectra too. Measurements after more than 500 days revealed no significant aging effects of the composites, which confirm their chemical stability.